Constructing the bonding interactions between endohedral metallofullerene superatoms by embedded atomic regulation. Issue 30 (27th July 2021) - Xie, Weiyu; Yu, Famin; Wu, Xiaochen; Liu, Zhonghua; Yan, Qiang; Wang, Zhigang
Abstract : Bonding types between endohedral metallofullerene (EMF) superatoms can be regulated by changing embedded atoms. Abstract : We present a possible principle that controls intercluster bonding through embedding different kinds of actinide atoms into the centre of fullerenes, thereby exhibiting different bonding forms. Moreover, these superatoms maintain the robustness of electronic structures.